SEMANTIK RAGAM MAKNA PADA JUDUL FILM AZAB DI INDOSIAR - Wahyu Oktavia (Universitas Sarjanawiyata Tamansiswa, 2019)
The research entitled â€œSemantic Variety of Meanings on The Title of The Film of Doom on Indosiar in 2018â€ aims to find out the semantic meanings contained in the title of the film doom on Indosiar. This study uses the method of listening and tapping which makes direct observations. This type of research is qualitative research whose data is analyzed based on a collection of the word. The results of the study showed that from 15 data of the doom movie title obtained from 4 synonym meanings, 2 acronym meanings, 2 meaning of dented shapes, 4 repeated word meanings, 3 figurative meanings and driving factors for the various writing languages.